“Education for Sustainable Democracy”, and “Education against Crisis of Democracy”: Rethinking John Dewey’s Conceptions of Democracy and Education - ISHIDA, Masaki (ANNALS OF THE SOCIETY FOR THE HISTORY OF SOCIAL THOUGHT, 2022)
This paper clarifies the relationship between democracy and education in John Dewey’s work by examining the transformation of his concept of democracy.   First, this paper focuses on the discussions in Dewey’s Democracy and Education (1916) and reveals his characterization of their relationship as “education for sustainable democracy.” I will show that Dewey takes the democratization of society as self-evident, and positions schooling as a means to maintain and sustain it. I will also show that Dewey tried to overcome the social divisions of the time by proposing an integration between civic and vocational education.   Secondly, I will focus on the transformation of Dewey’s theory of democracy in the 1930s and show that it was transformed into an “education against the crisis of democracy.” In other words, I argue that Dewey’s democracy turned into a “socialist democracy” to fight the Great Depression, on the one hand, and, on the other hand, it became more and more a “militant democracy” fighting against totalitarianism. This paper clarifies the transformation of Dewey’s concept of democracy and education and discusses its possibilities and limitations.